Efficacy and tolerability of once-monthly oral ibandronate in postmenopausal osteoporosis: 2 year results from the MOBILE study. - Reginster, J; Adami, S; Lakatos, P; Greenwald, M; Stepan, J; Silverman, S; Christiansen, C; Rowell, L; Mairon, N; Bonvoisin, B; Drezner, M; Emkey, R; et al. (2006)
BACKGROUND: Reducing bisphosphonate dosing frequency may improve suboptimal adherence to treatment and therefore therapeutic outcomes in postmenopausal osteoporosis. Once-monthly oral ibandronate has been developed to overcome this problem. OBJECTIVE: To confirm the 1 year results and provide more extensive safety and tolerability information for once-monthly dosing by a 2 year analysis. METHODS: MOBILE, a randomised, phase III, non-inferiority study, compared the efficacy and safety of once-monthly ibandronate with daily ibandronate, which has previously been shown to reduce vertebral fracture risk in comparison with placebo. RESULTS: 1609 postmenopausal women were randomised. Substantial increases in lumbar spine bone mineral density (BMD) were seen in all treatment arms: 5.0%, 5.3%, 5.6%, and 6.6% in the daily and once-monthly groups (50 + 50 mg, 100 mg, and 150 mg), respectively. It was confirmed that all once-monthly regimens were at least as effective as daily treatment, and in addition, 150 mg was found to be better (p<0.001). Substantial increases in proximal femur (total hip, femoral neck, trochanter) BMD were seen; 150 mg produced the most pronounced effect (p<0.05 versus daily treatment). Independent of the regimen, most participants (70.5-93.5%) achieved increases above baseline in lumbar spine or total hip BMD, or both. Pronounced decreases in the biochemical marker of bone resorption, sCTX, observed in all arms after 3 months, were maintained throughout. The 150 mg regimen consistently produced greater increases in BMD and sCTX suppression than the 100 mg and daily regimens. Ibandronate was well tolerated, with a similar incidence of adverse events across groups. CONCLUSIONS: Once-monthly oral ibandronate is at least as effective and well tolerated as daily treatment. Once-monthly administration may be more convenient for patients and improve therapeutic adherence, thereby optimising outcomes.